MULTIMODALITY IMAGING OF COVID-19 PNEUMONIA : A SYSTEMATIC REVIEW - Nisa', Khoirun; Miska, Ari (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Reversible transcription polymerase chain reaction (RT-PCR) nasopharyngeal or oropharyngeal swab tests that yield a positive result can establish the diagnosis of COVID-19. Due to the high prevalence of false-negative findings, especially in the early stages of the disease, and the patchy availability of testing, a methodical approach to diagnosis that incorporates radiologic imaging is required. Aims : This systematic review is to review the multimodality imaging of patients with COVID-19 pneumonia. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SAGEPUB, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 22.043 articles, whereas the results of our search on SAGEPUB brought up 19.007 articles. The results of the search conducted for the last year of 2014 yielded a total 173 articles for PubMed and 98 articles for SAGEPUB. In the end, we compiled a total of 6 papers, 5 of which came from PubMed and 1 of which came from SAGEPUB. We included five research that met the criteria. Conclusion: In summary, owing to the SARS-CoV-2 pandemic, it is critical to understand the typical and atypical imaging features of COVID-19 pneumonia as well as how they change over time on CXR and HRCT. When evaluating hospitalized and critically sick patients in a serial fashion, as well as in places with high levels of contagion, computed tomography (CXR) may be the initial imaging modality employed